2001
DOI: 10.1093/jnci/93.2.121
|View full text |Cite
|
Sign up to set email alerts
|

Cancer in Patients With Ataxia-Telangiectasia and in Their Relatives in the Nordic Countries

Abstract: We confirmed the previously recognized high risk of lymphoma and leukemia in A-T patients. Our data are also consistent with an increased risk of breast cancer among blood relatives of A-T patients. The epidemiologic findings suggest, however, that, even if ATM mutations are responsible for some breast cancer cases, ATM is a relatively weak genetic risk factor for the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
134
2
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(144 citation statements)
references
References 19 publications
6
134
2
2
Order By: Relevance
“…Most of the epidemiological studies of AT relatives report an increased risk of breast cancer at younger ages, below 45-55 years (Inskip et al, 1999;Janin et al, 1999;Olsen et al, 2000), contrary from Athma et al (1996). In the present study, only 150 of the patients analysed were below the age of 55 at time of diagnosis, which may explain the low frequency of mutations seen.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…Most of the epidemiological studies of AT relatives report an increased risk of breast cancer at younger ages, below 45-55 years (Inskip et al, 1999;Janin et al, 1999;Olsen et al, 2000), contrary from Athma et al (1996). In the present study, only 150 of the patients analysed were below the age of 55 at time of diagnosis, which may explain the low frequency of mutations seen.…”
Section: Discussioncontrasting
confidence: 65%
“…Heterozygotes are clinically asymptomatic, but a number of epidemiological studies in AT families have noted a significant increase in cancer incidence, in breast cancer particularly (Easton, 1994;Athma et al, 1996;Inskip et al, 1999;Janin et al, 1999;Olsen et al, 2000). The relative risk was in the range 1.5-9, depending on population, age and family relation.…”
mentioning
confidence: 99%
“…41,42 The population attributable proportion of the recessive ATM gene to breast cancer is equally large. 43 A number of studies have reported on the associations of HLA class II alleles with susceptibility to cervical cancer. 44 -46 However, these associations (with different grades of neoplasia or invasive cervical cancer) appear to be relatively weak and it remains to be determined whether they account for a significant proportion of the heritability of the disease.…”
Section: Heritable Effectsmentioning
confidence: 99%
“…Subsequent studies have provided inconclusive and/or inconsistent data about whether/which additional cancers are associated with ATM heterozygosity (Geoffroy-Perez et al, 2001;Olsen et al, 2001;Thompson et al, 2005b). Further, larger studies will be required to investigate the role of ATM in susceptibility to cancers other than breast cancer.…”
Section: Other Phenotypic Features In Atm Heterozygotesmentioning
confidence: 99%